Biochemical Roles of Eukaryotic Cell Surface Macromolecules - Chakrabarti, Abhijit; Surolia, Avadhesha (Advances in Experimental Medicine and Biology, 2015)
Consists of critical reviews and original research papers from the 2014 International Symposium on the "Biochemical Role of Eukaryotic Cell Surface Macromolecules". Topics covered include: · neurochemical and biochemical analysis of cell surface glycoconjugates · membrane skeletal organization · GPCRs and other receptors · biophysical approaches to study membrane interactions · glycoconjugate metabolism · dysregulation · molecular mechanisms involved in cell-cell and cell-matrix interaction · glycans in infectious and neurological diseases · cancer and glycosyltransferases as drug targets.